Synthesis and Antitubercular Activity of 4, 5‐Disubstituted N1‐(5′‐deoxythymidin‐5′‐yl)‐1, 2, 3‐triazoles. Issue 28 (30th July 2020) - Kumar, Rajesh; Bimal, Devla; Kavita,; Kumar, Manish; Mathur, Divya; Maity, Jyotirmoy; Singh, Sunil K.; Thirumal, M.; Prasad, Ashok K.
Abstract: Synthesis of fifteen C 4 ‐aroyl‐ C 5 ‐aryl‐ N 1 ‐(5′‐deoxythymidin‐5′‐yl)‐1, 2, 3‐triazoles have been reported starting from azidation of 5′‐ p ‐toluenesulfonyloxythymidine followed by azide‐alkene oxidative cycloaddition reaction of the resulted 5′‐azido‐5′‐deoxythymidine with 1, 3‐diarylpropenones in dimethylformamide (DMF) in the presence of tetra‐ n ‐butylammonium hydrogen sulfate ( n ‐Bu4 N + HSO4 −, TBAHS) as catalyst in 60 to 79% overall yields. Further, they were also synthesized by one pot sequential reaction of tosylated thymidine with sodium azide in DMF and then with 1, 3‐diarylpropenones in presence of n ‐Bu4 N + HSO4 − in superior yield of 70 to 95% than 60 to 79% in two step procedure. All fifteen synthesized compounds were screened for their in vitro anti Mycobacterium tuberculosis activity against sensitive reference strain H37Rv and multi drug resistant (MDR) clinical isolate 591, and found to exhibit minimum inhibitory concentration (MIC) ranging from 2 to 15 μg/mL, which was equivalent to the MIC of first line anti‐tubercular drug streptomycin. All compounds qualify for their drug likeness when their physicochemical parameters were assessed using online MolSoft and Lipinski filter software, except their molecular weight. The cytotoxicity of potent compounds evaluated human monocytic cell line THP‐1 by 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyl‐2 H ‐tetrazolium bromide (MTT) assay was found to be less as compared to the first line drug, isoniazid. Abstract : Fifteen C 4 ‐aroyl‐ C 5 ‐aryl‐ N 1 ‐(5′‐deoxythymidin‐5′‐yl)‐1, 2, 3‐triazoles have been synthesized over two steps, starting from 5′‐ p ‐toluenesulfonyloxythymidine. One pot sequential reaction produced the same compounds in superior yields of 70 to 95%. All compounds were screened for their in vitro anti Mycobacterium tuberculosis activity against sensitive reference strain H37Rv and multi drug resistant (MDR) clinical isolate 591, and they were found to exhibit MIC ranging from 2 to 15 μg/mL. The cytotoxicity of potent compounds evaluated on human THP‐1 cell line by MTT assay was found to be less as compared to the first line drug, isoniazid.